2019
DOI: 10.3390/plants8110494
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Anti-Candida spp. Activity of Plant-Derived Products

Abstract: Candidiasis therapy, especially for candidiasis caused by Candida non-albicans species, is limited by the relatively reduced number of antifungal drugs and the emergence of antifungal tolerance. This study evaluates the anticandidal activity of 41 plant-derived products against Candida species, in both planktonic and biofilm cells. This study also evaluates the toxicity and the therapeutic action of the most active compounds by using the Caenorhabditis elegans–Candida model. The planktonic cells were cultured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 43 publications
2
59
0
1
Order By: Relevance
“…Studies have shown that LCEO is a cell wall-active agent and can cause cell membrane damage of S. aureus [ 11 ], and our current results were similar. S. aureus is a Gram-positive bacteria and A. baumannii 17 is a Gram-negative bacteria, which again showed that LCEO has spectral antimicrobial activity [ 7 , 53 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that LCEO is a cell wall-active agent and can cause cell membrane damage of S. aureus [ 11 ], and our current results were similar. S. aureus is a Gram-positive bacteria and A. baumannii 17 is a Gram-negative bacteria, which again showed that LCEO has spectral antimicrobial activity [ 7 , 53 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on in vitro and in vivo data, echinocandins and amphotericin B solutions are the most promising combination-based and/or antifungal lock strategies [ 19 ]. Further innovative therapeutic approaches may be the natural products-based treatments [ 22 , 23 ]. One of the more well-studied compounds is carbohydrate-derived fulvic acid as a heat stable colloidal material, which has an inhibitory effect on Candida and bacterial biofilm formation [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…elegans has been extensively used for studying several dimorphic fungi of clinical relevance. The most devastating and pathogenic dimorphic fungus that has been adequately explored with this nematode model is Candida albicans (Hans et al, 2019a;Hans et al, 2019b;Song et al, 2019;Venkata et al, 2020) and a few other non-albicans species such as C. tropicalis (Brilhante et al, 2016;Feistel et al, 2019;Pedroso et al, 2019), C. krusei (De Aguiar Cordeiro et al, 2018Kunyeit et al, 2019), and C. auris (Eldesouky et al, 2018a;Mohammad et al, 2019). Another important clinical dimorphic fungus, Taloromyces (Penicillium) marneffei, has also been studied in a C. elegans model for both virulence tests and antifungal agent efficacy evaluations (Huang et al, 2014;Sangkanu et al, 2021).…”
Section: Application Of C Elegans For Dimorphic Fungi Studiesmentioning
confidence: 99%